2020
DOI: 10.1051/e3sconf/202017509013
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of degraded mountain pastures of the Сentral Сaucasus by targeted sowing of seeds of perennial grasses

Abstract: The unsystematic use of mountain pastures with overgrazing of grasses has led to a change in the ecological balance of agrolandscapes, in which 80-85% of the Central Caucasus lands have turned into a state of varying degrees of degradation. In these cases, an important measure in the restoration of degraded mountain forage lands is the sowing of perennial grasses into sparse grass and on bare soil, which increases stiffness. Therefore, the development and creation of a seeder for targeted seeding of grass mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Furthermore, estimates of grass forage yields are important for the determination of the grazing capacity of a grassland ecosystem [2]. In addition, the knowledge of available forage enables land managers to make informed decisions about stocking rates and grazing management practices to prevent overgrazing and maintain the health of grasslands [3]. Yield estimates are important for understanding the relationship between climate and forage growth, as research has shown that forage yield is closely related to climatic factors such as precipitation [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, estimates of grass forage yields are important for the determination of the grazing capacity of a grassland ecosystem [2]. In addition, the knowledge of available forage enables land managers to make informed decisions about stocking rates and grazing management practices to prevent overgrazing and maintain the health of grasslands [3]. Yield estimates are important for understanding the relationship between climate and forage growth, as research has shown that forage yield is closely related to climatic factors such as precipitation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The following sample sizes were available for those species directly used in model training: 61 for orchard grass (Dactylis glomerata), 138 for intermediate wheatgrass IWG (Thinopyrum intermedium), 325 for bluebunch wheatgrass BBWG (Pseudoroegneria spicata), and 457 for tall fescue (Festuca arundinacea). 3 Shandon CAL 1 TF_CAL23_1 tall fescue Shandon CAL 2 TF_CAL23_2 orchard grass 4 Shandon CAL 1 ORC_CAL23_1 orchard grass Shandon CAL 2 ORC_CAL23_2…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to improve pastures by sowing seeds under cover crops and on turf (Himmelbauer et al, 2013;Bathgate, Revell, and Kingwell, 2009). Currently, the radical improvement of pastures, including a full range of operations to create a new grass shank by sowing seeds of perennial grasses requires significant financial costs and is carried out very rarely (Fulkerson and Lowe, 2022;Soldatov et al, 2020;Zotov et al, 2012). The majority of technologies for restoring the biological productivity of natural grasslands are based on scattered grass seeding or direct seeding, which involves cutting furrows in the turf and seeding grass seeds.…”
Section: Introductionmentioning
confidence: 99%